Impact of Historic Migrations and Evolutionary Processes on Human Immunity - Domínguez-Andrés, Jorge; Netea, Mihai G. (Trends in immunology, 2019)
The evolution of mankind has constantly been influenced by the pathogens encountered. The various populations of modern humans that ventured out of Africa adapted to different environments and faced a large variety of infectious agents, resulting in local adaptations of the immune system for these populations. The functional variation of immune genes as a result of evolution is relevant in the responses against infection, as well as in the emergence of autoimmune and inflammatory diseases observed in modern populations. Understanding how host–pathogen interactions have influenced the human immune system from an evolutionary perspective might contribute to unveiling the causes behind different immune-mediated disorders and promote the development of new strategies to detect and control such diseases. Human evolution has been constantly influenced by pathogens; therefore, a great number of human genes linked to immune functions and immunity-related disorders have evolved along with humans.The heterogeneity in the immune response to infectious diseases across different populations is under genetic control and is the result of evolutionary processes.Genetic variants that have been under evolutionary pressure can contribute to explaining the differences in the susceptibility to diseases observed across different populations.The ancestry of individuals from different populations across the globe greatly influences their possibility of developing certain autoimmune diseases and inflammatory disorders.The lifestyle of Western societies affects the symbiotic relationships between humans, viruses, and other organisms and might contribute to the rise of certain autoimmune and inflammatory diseases.